Focal segmental membranoproliferative glomerulonephritis: a histological variant of Denys-Drash Syndrome - Karmila, A. B.; Yap, Y. C.; Appadurai, M.; Oh, L.; Fazarina, M.; Abd Ghani, F.; Ariffin, H. (Taylor & Francis, 2019)
Introduction: Denys-Drash Syndrome (DDS) consists of a triad of pseudohermaphroditism, Wilms’tumor and nephropathy. This condition may manifest as a complete triad or in an incomplete form; with either one or a combination of the above features. The characteristic glomerular abnormality in DDS is diffuse mesangial sclerosis (DMS). Case report: We report two cases of DDS with focal membranoproliferative glomerulonephritis (MPGN). Both of our cases were males with ambiguous genitalia. They had a similar heterozygous germline mutation in exon 9 of WT1, c.1180C>T, p.R394W; a known mutation hotspot for DDS. Case 1 had nephropathy at the age of 4 years and Case 2 at 2.5 years with different rates of progression to end-stage renal failure. Conclusion: Our findings, in combination with other reports, illustrate the clinicopathological heterogeneity of DDS. There are no universal recommendations for optimal management of patients with DDS due to the inability to accurately predict affected individuals’ progress.